Chiral Lewis Base Activation of Acyl and Related Donors in Enantioselective Transformations (n → π) - Murray,JI; Heckenast,Z; Spivey,AC (2016)
The role of Lewis bases in acylation reactions has been studied from both synthetic and mechanistic standpoints with a particular recent focus on enantioselective variants mediated by single enantiomer chiral Lewis bases deployed substoichiometrically. The modern-era of research into asymmetric enantioselective nucleophile-catalyzed acyl transfer using designed nucleophiles was initiated in the mid-1990s by the groups of Vedejs and Fu. This group developed chiral ferro-cenyl 4-dialkylaminopyridine derivatives first for the kinetic resolution (KR) of sec-alcohols and for an array of other transformations. Since the 1980s, the synthetic potential of enantioselective acylation has been well established in the context of fine chemical synthesis as a result of the development of biocatalytic processes that rely on hydrolytic enzymes. Cognizant that both bases and nucleophiles catalyze the acylation of alcohols using anhydrides and that alkyl phosphines in particular display weak basicity and strong nucleophilicity, Vedejs and Diver published a study of the utility of phosphines as acyl transfer catalysts.